2019
DOI: 10.1177/000313482008600226
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Trauma Patients Screened for Venous Thromboembolism Have a Higher Risk Profile with Lower Rate of Pulmonary Embolism: A Five-Year Single-Institution Experience

Abstract: Deep vein thrombosis (DVT) is linked to reimbursements and publicly reported metrics. Some hospitals discourage venous duplex ultrasound (VDUS) screening in asymptomatic trauma patients because they often find higher rates of DVT. We aim to evaluate the association between lower extremity (LE) VDUS screening and pulmonary embolism (PE) in trauma patients. Trauma patients admitted to an urban Level-1 trauma center between 2010 and 2015 were retrospectively analyzed. We characterized the association of asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…27 The theoretical value of active screening is that it allows for earlier detection of thrombosis and the initiation of anticoagulation if appropriate. 28 For example, an RCT of approximately 2000 trauma patients at moderate to high risk of F I G U R E 3 Cumulative probability of thromboembolic event for each intervention group. There were 149 patients were included in the analysis, with 50 patients in the placebo group, 49 patients in the 2-g TXA group, and 50 patients in the 4-g TXA group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The theoretical value of active screening is that it allows for earlier detection of thrombosis and the initiation of anticoagulation if appropriate. 28 For example, an RCT of approximately 2000 trauma patients at moderate to high risk of F I G U R E 3 Cumulative probability of thromboembolic event for each intervention group. There were 149 patients were included in the analysis, with 50 patients in the placebo group, 49 patients in the 2-g TXA group, and 50 patients in the 4-g TXA group.…”
Section: Resultsmentioning
confidence: 99%
“…A recent survey of 317 individual surgeons reported a wide variation in opinions regarding deep vein thromboembolism screening in asymptomatic trauma patients (53% agree, 36% disagree, and 11% neither agree nor disagree) 27 . The theoretical value of active screening is that it allows for earlier detection of thrombosis and the initiation of anticoagulation if appropriate 28 . For example, an RCT of approximately 2000 trauma patients at moderate to high risk of thromboembolism reported a significant reduction in pulmonary embolism incidence using screening duplex ultrasound of the lower extremities 29 .…”
Section: Discussionmentioning
confidence: 99%
“…4,41 The increased DVT rate observed in the US group was primarily due to the diagnosis of distal DVT and, to a much lesser degree, proximal DVT (11.7% more vs. 1.1% more, respectively), similar to other findings. 26,27 It could therefore be argued that the diagnosis of proximal DVT is less susceptible to surveillance bias and remains an important target for the implementation of routine DUS. While this study was not designed to evaluate the management of the distal DVT, it is essential to acknowledge the lack of agreement surrounding its clinical impact and management.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it was also possible that the author found more upper limb DVT by using more frequent ultrasound examinations than before, which was the so‐called “more examination, more discovery” 75 . Johnson et al 76 . studied 1021 patients who had received intravenous ultrasound screening more than once during hospitalization.…”
Section: The Incidence Of Dvt In Upper Extremity Fractures May Not Be...mentioning
confidence: 99%
“…Meanwhile, it was also possible that the author found more upper limb DVT by using more frequent ultrasound examinations than before, which was the so-called "more examination, more discovery" 75 . Johnson et al 76 studied 1021 patients who had received intravenous ultrasound screening more than once during hospitalization. The results showed that the more examinations, the higher the incidence of distal DVT and the lower the incidence of PE, which had nothing to do with the incidence of proximal DVT, indicating that the more ultrasound examinations that occurred, the more the total incidence of DVT.…”
Section: Prevention Of Postthrombotic Syndrome May Be Anmentioning
confidence: 99%